VD_FINDINFO HC / 2009 / 141 vom 27. April 2009 - VD Tribunal cantonal (2009)
ACTION EN PARTAGE SUCCESSORAL, PARTAGE SUCCESSORAL, RECTIFICATION DE LA DÉCISION | 604 CC, 302 al. 1 CPC, 489 CPC, 567 CPC, 586 al. 1 CPC